Near-infrared broadband Si:H/SiO2 multilayer gratings with high tolerance to fabrication errors. (12th May 2020) - He, Tao; Zhang, Jinlong; Jiao, Hongfei; Wang, Zhanshan; Cheng, Xinbin
Abstract: Si:H and TiO2 multilayer dielectric gratings (MDGs) were studied comparatively to highlight the influence of refractive indices on fabrication tolerances, including tolerances for grating width errors and cross-sectional shape errors. The fabrication tolerance of Si:H MDGs is two to four times greater than that of TiO2 MDGs, because the higher refractive index of Si:H has a stronger ability to restrain electric fields. It was further revealed in these studies that a Si:H MDG with positive trapezoidal errors has minor influence on high diffraction efficiency bandwidth. Finally, a Si:H MDG was prepared without iterative corrections. Although large fabrication errors of grating width and cross-sectional shape existed, the MDG still had a 146 nm bandwidth with diffraction efficiency over 97%, which verifies the robustness of the proposed Si:H MDG.